The Effect of MSME Credit and Government AID on MSME Growth and Reduction of Poverty Rate in the City of Balikpapan - Siwi Tri Wijayanti; Aji Sofyan Effendi; Diana Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to determine the effect of MSME credit and government assistance on MSME growth and reducing poverty rates in Balikpapan City. The analytical tool used is path analysis. Path analysis is an analytical method used in research to test the influence of independent variables on dependent variables, including indirect influences through mediating intervening variables. This method is more complex than ordinary regression analysis and requires in-depth understanding. The analysis application used in this research is the SPSS v25 application. The results of research on the provision of banking credit on the growth of MSMEs in Balikpapan City have a positive and significant effect. It can be concluded that banking in Balikpapan City can grow and develop MSMEs in Balikpapan City. Providing Bank Credit to Poverty Alleviation has no direct and insignificant effect, this means that the contribution of providing credit cannot necessarily reduce the poverty rate in Balikpapan City. The Balikpapan City Government's assistance for the growth of MSMEs is positive and significant, this means that the assistance is very effective in directly developing the growth of MSMEs in Balikpapan City. Balikpapan City Government's assistance to the poverty level in Balikpapan City is negative and significant. It can be concluded that the Balikpapan City Government's policy instrument by providing assistance to MSMEs will be able to reduce the poverty rate in Balikpapan City. It can be concluded that the growth of MSMEs in Balikpapan City has a negative effect on reducing the poverty rate, meaning that the more MSMEs grow, the poverty rate will decrease.